2011
DOI: 10.2174/156802611794863607
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Motions of the E. coli Glucose-Galactose Binding Protein Studied Using Well-Sampled Semi-Atomistic Simulations

Abstract: The E. coli glucose-galactose chemosensory receptor is a 309 residue, 32 kDa protein consisting of two distinct structural domains. We used two computational methods to examine the protein’s thermal fluctuations, including both the large-scale interdomain movements that contribute to the receptor’s mechanism of action, as well as smaller-scale motions. We primarily employ extremely fast, “semi-atomistic” Library-Based Monte Carlo (LBMC) simulations, which include all backbone atoms but “implicit” side chains. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 35 publications
(83 reference statements)
1
10
0
Order By: Relevance
“…Collective motions would have to occur with correlation times between 10 –4 s and 10 –8 s since the molecular alignment tensor (derived from RDC data) differs significantly from the rotational diffusion tensor (derived from NMR relaxation data) while order parameters S 2 are not significantly reduced. This is consistent with recent semiatomistic molecular simulations . Upon glucose binding, a general decrease in S 2 is observed that proves such hinge motions persist in holo GGBP, however, on a faster nanosecond time scale (≤12 ns).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Collective motions would have to occur with correlation times between 10 –4 s and 10 –8 s since the molecular alignment tensor (derived from RDC data) differs significantly from the rotational diffusion tensor (derived from NMR relaxation data) while order parameters S 2 are not significantly reduced. This is consistent with recent semiatomistic molecular simulations . Upon glucose binding, a general decrease in S 2 is observed that proves such hinge motions persist in holo GGBP, however, on a faster nanosecond time scale (≤12 ns).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with recent semiatomistic molecular simulations. 56 Upon glucose binding, a general decrease in S 2 is observed that proves such hinge motions persist in holoGGBP, however, on a faster nanosecond time scale (≤12 ns). The neat entropic contribution found reflects an increase in dynamics that shall be attributed to coupled motions between the two domains.…”
Section: ■ Discussionmentioning
confidence: 88%
“…Thus, all protein atomic positions are tracked in the present LBMC implementation, unlike in our previous LBMC protein simulations. 34,36 …”
Section: Methodsmentioning
confidence: 99%
“…Library approaches can offer tremendous efficiency for small, implicitly solvated peptides, 35,3840 and also great flexibility in constructing and sampling protein models. 34,36,37 Memory can also be exploited in molecular simulations by tabulating interactions among molecules or fragments, which can speed up calculations and smooth interactions. 41 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation